Factors Affecting Talent Management Strategies in Construction Companies - Agustinus Setyawan; Alden Nelson (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Business competition in construction companies is getting tighter and human resource management is one of the essential things in supporting the company’s competitiveness. The right strategy is needed if a company wants to build a strong team by forming highly talented people in a company. This study aims to analyze the influence of management commitment, organizational culture, reward system, career management, and knowledge management on talent management strategy. The method used in sample selection is a non-probability method with purposive sampling technique and the population is employees who work in the offshore construction industry in Batam. This study uses a questionnaire to frontline management employees of the offshore construction industry and the rate of return of the questionnaire is 50 sheets. The statistical method used to test the hypothesis is multiple regression using the SPSS program. The results of the research conducted indicate that the management commitment and knowledge management variables have a significant positive effect on the talent management strategy, while the organizational culture variables, reward systems, and career management do not have a significant positive effect on the talent management strategy.